Public schools and critical education: Alternative education policy in Indonesia - Rahmad Rafid; Riski Febria Nurita; Dedi Dores (Journal of Social, Humanity, and Education, 2025)
Purpose: This study analyzes the implementation of community school policies within the framework of critical education, based on Presidential Instruction No. 8 of 2025 on the eradication of extreme poverty. Research Methodology: This research uses qualitative methods based on policy studies to evaluate the effectiveness, challenges, and opportunities of community school programs in supporting poverty reduction through education. Results: “Sekolah Rakyat” can build critical awareness in poor communities, strengthen local participation, and integrate education with local wisdom. However, the success of this program still faces the challenges of inter-agency coordination, limited human resources, and inadequate facilities. Therefore, sustainable policy support, cross-sector collaboration, and community engagement are essential to strengthen the impact of Community Schools as a tool of social transformation and inclusive education. Conclusions: The implementation of "Sekolah Rakyat" as an alternative education policy in Indonesia has great potential to reduce social and economic disparities, especially for the poor and marginal communities. Paulo Freire's critical education approach provides not only practical knowledge but also critical thinking skills and social awareness to play a role in social change. Education based on local wisdom is considered relevant to the needs of the community. Limitations: This research shows that the "people's school" policy has great potential as a strategy to reduce extreme poverty through education. The government needs to push the mainstream of alternative education policies based on social empowerment into national policies. Contribution: The study emphasizes that "Sekolah rakyat" are not only Centers for academic learning, but also for life skills, character development, and social awareness.